2018
DOI: 10.2741/4583
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of i p57 sup kip2 sup i expression during development differentiation and disease

Abstract: p57 is the most complex member of the CIP/KIP family of cyclin-dependent kinase inhibitors and plays a fundamental role in regulating cell cycle and differentiation during mammalian development. Consistently with a key role for p57 in the spatial and temporal control of cell proliferation, its expression is fine-tuned by multiple regulatory mechanisms, resulting in a tissue-, developmental phase- and cell type-specific pattern. Moreover, is an imprinted gene, further supporting the importance of its proper exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Consistent with the critical importance of the proper p57 expression dosage, not only the paternal allele is ubiquitously and permanently silenced, but also the maternal allele is tightly and finely regulated during development and differentiation [16]. Our work in muscle cells revealed that KvDMR1, in addition to control the silencing of the imprinted p57 paternal allele, is also involved in preventing the expression of the functional p57 maternal allele until differentiation occurs [17, 18].…”
Section: Introductionmentioning
confidence: 65%
“…Consistent with the critical importance of the proper p57 expression dosage, not only the paternal allele is ubiquitously and permanently silenced, but also the maternal allele is tightly and finely regulated during development and differentiation [16]. Our work in muscle cells revealed that KvDMR1, in addition to control the silencing of the imprinted p57 paternal allele, is also involved in preventing the expression of the functional p57 maternal allele until differentiation occurs [17, 18].…”
Section: Introductionmentioning
confidence: 65%
“…Preodontoblasts are the polarized cells beginning to stop their proliferation and acquire differentiation, while mature odontoblasts are matrix-producing cells with their differention almost completed. It is generally thought that there exists an inverse relationship between cell proliferation and differentiation, and p57 is a cell cycle arrest gene and is associated with exit from the cell cycle and entry into differentiation (Rossi et al 2018 ). Thus it is explicable that we observed intensely p57 expression in immature odontoblasts, and reduced expression in mature odontoblasts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The protein was identified by sequence homology with the other two members of the family, i.e., p21 Cip1/WAF1 and p27 Kip1 [1,2]. Differently from p21 Cip1/WAF1 and p27 Kip1 , scarce information has been accumulated on p57 structural characteristics despite more than 25 years having passed since its initial identification [3][4][5][6][7][8]. Certainly, what has definitely been demonstrated is that all CIP/Kip members present some structural features that are necessary to exert their function in the regulation of the cell division cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Besides this inhibitory activity, p57 and its siblings have been reported as being able to promote the assembly of the Cyclin D-CDK4/6 complex, a striking characteristic that allows them to be considered more comprehensively as major cell cycle regulators [6][7][8][9]. The N-terminal domain is also involved in the interaction with transcription factors such as b-Myb and MyoD, controlling gene expression [5]. In contrast, they exhibit strongly divergent central and carboxy-terminal domains.…”
Section: Introductionmentioning
confidence: 99%